AN ENHANCEMENT APPROACH FOR OBJECT DETECTION IN LOW QUALITY IMAGES USING LOCAL BINARY PATTERN (L.B.P.) - Abdul Basit Abdul Majeed Quraishi; Prof. Y. B. Jadhao (International Engineering Journal For Research & Development, 2021)
With significant increase in desire of multimedia technology and entrance into the digital age an ample breadth of image data must be handled to be saved in a proper manner. For the proper detecting of image data or useful objects system needs to be develop for perfecting videotape quality, discovery and shadowing of object in any videotape. Videotape is a gathering of consecutive filmland with a harmonious time interlude. So videotape can give further data about composition when situations are changing regarding time. Hence, physically taking care of recordings is entirely unconceivable. So there's a need of a motorized contrivance to handle these recordings.